Assessing the current feces identification method of the European otter Lutra lutra. Issue 1 (25th January 2021) - Andersen, Liselotte Wesley; Schousgaard, Henriette Sallo; Kahlert, Johnny; Linnet, Anton; Jensen, Ole Hyttel; Thomsen, Erik Arnfred; S⊘rensen, Flemming; Baag⊘e, Hans J⊘rgen; Frikke, John; Jacobsen, Henrik; Håkansson, Bo; Loeschcke, Volker; et al.
Abstract : In the past the European otter Lutra lutra was distributed throughout most of Europe but since the 1980s its distributional range has been reduced. Currently, the otter population is increasing. Conservation efforts have been implemented, however due to the natural elusiveness of the species it is difficult to monitor. Non‐invasive sampling has proven to be the most effective method to derive population parameters such as presence/absence, genetic variability and population structure in European otters. The method to collect non‐invasive samples is robust and provides reliable data. This study investigates the validity of the present state‐of‐the‐art method of identifying otter feces, and suggests modifications and improvements of the method. Results from the comparison of field collected data and data derived from a blind test show that the method is applicable in areas abundant with otters, however the method loses its power in the periphery of the distributional range. In these areas, it would be relevant to supplement traditional sampling with DNA analysis to verify the identification of the sample.